Impact of the COVID-19 in Tourism Industry in Nepal and Policy Recommendation - Khanal, Bishnu Prasad (Journal of Tourism & Adventure, 2020)
For the first time in history, almost all the domestic and international tourism destinations have restrictions for travel worldwide because of corona virus pandemic. Corona virus disease calls the COVID-19 pandemic is an ongoing problem in more than 210 countries in the world. The purpose of this study is to find the tourism impact of COVID-19 in Nepal and purpose recommendations for the preparation of evidence based policy and strategies for further development of the tourism industry in Nepal. Secondary data used in this study were obtained from the ministry of tourism in Nepal and other various web sources and primary data were collected from the online survey and collected 52 samples. They are involved in the hospitality, education & consulting, travel & tours, adventure & expedition, trekking agencies, and government officials from national tourism originations. The study highlights that the tourism contribution in Nepal’s GDP (Gross Domestic Product) as a significant sector that has a linkage with other sectors. Also, the Nepalese tourism industry is dependent on international factors and the Nepal tourism industry highly relies on foreign tourists and cancellation of the mountain climbing permits for the year 2020, affects the income of foreign currency as building the capacity of stakeholders and public-private partnership initiatives to promote and work together to develop and manage in future tourism fields. well as the local economy, the loss of thousands of jobs in the tourism sector and others sectors. Overall analyses suggest that building the capacity of stakeholders and public-private partnership initiatives to promote and work together to develop and manage in future tourism fields.